PENGELOLAAN PEMBELAJARAN DI SEKOLAH MENENGAH PERTAMA AL-FAQIH SUMBER NYAMPLONG KOWEL PAMEKASAN - Badrud Tamam; Zainol Hasan; Hilmi Qosim Mubah (re-JIEM (Research Journal of Islamic Education Management), 2020)
SMP Al-Faqih Nyamplong Kowel Pamekasan is one of the middle-level institutions which is directly under the auspices of the Islamic boarding schools in the Pamekasan sub-district. The institute is currently making efforts to improve the quality of learning such as conducting learning planning as outlined in the Learning Program Plan (RPP), the results of the study show that: First, 1) The teacher does the planning first by setting clear and concrete objectives, 2) The teacher organizes learning strategies by determining the types of methods, media, learning resources and teaching and learning facilities. Second, 1) Students are more active and learning activities are more fun, 2) Students can increase their knowledge of the material that has been and will be conveyed by the teacher. Third, 1) The supporting factors are; a) Learning activities are more effective and fun, b) Students have an interest and motivation to learn better. 2) Inhibiting factors for learning management strategies at Al-Faqih Middle School, namely; a) Environmental factors that are under the auspices of Islamic boarding schools, b) The lack of adequate facilities and infrastructure.